-7+4(c+8)=-2(c-1)

Simple and best practice solution for -7+4(c+8)=-2(c-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+4(c+8)=-2(c-1) equation:



-7+4(c+8)=-2(c-1)
We move all terms to the left:
-7+4(c+8)-(-2(c-1))=0
We multiply parentheses
4c-(-2(c-1))+32-7=0
We calculate terms in parentheses: -(-2(c-1)), so:
-2(c-1)
We multiply parentheses
-2c+2
Back to the equation:
-(-2c+2)
We add all the numbers together, and all the variables
4c-(-2c+2)+25=0
We get rid of parentheses
4c+2c-2+25=0
We add all the numbers together, and all the variables
6c+23=0
We move all terms containing c to the left, all other terms to the right
6c=-23
c=-23/6
c=-3+5/6

See similar equations:

| 3(x-1)+4x=4 | | x-2(1/4)(x-1/2)=1/6(2x+1)+1/3 | | 7y+-4y=-18 | | 8+.4x=4+.6x​ | | 11–5a=51 | | 6x-20=-14x+4 | | 3^2+10x–117=0 | | 5x-7=4x-1= | | 1-5x/8=3 | | 350+50x=800 | | 27-15=2(x-3)= | | 1.4t(t-3.1)=5.8 | | 5x2x2=10x5 | | 24=8x-4(x-8) | | 7g=9g−2g | | 12=10+x/5 | | 1.06g+-3=0.71 | | 5x+23+4x+31=180 | | x/8-x/9=9/8 | | 4a=3+11 | | 6x+30x-22x=392 | | 15-6p=-3(5p-4) | | 3x2+10x–117=0 | | -8=4n-8(1+3n) | | x+4/5+3x+3/2=4 | | (1/7)x+10=2x | | x+55+65+70=180 | | 2m+8=5m–10 | | 31.5=6.3t | | 1-3(9x+3)=3x+1= | | 0-42=3m | | x+55+65+75=180 |

Equations solver categories